Study of HER2 Expression by Immunohistochemistry in Papillary Urothelial Carcinoma of Urinary Bladder and its Comparison in Low Grade and High Grade Histological Subtypes - Azmat, Henna (International Journal of Pathology, 2023)
Introduction: HER2 protein expression in various carcinomas has a prognostic value. In urothelial carcinoma also, it has been found to be of prognostic and predictive importance. Like in other carcinomas, the search for HER2 expression has mainly focused on the utilization of the target therapies such as Trastuzumab against HER2 positive urothelial carcinomas. Objective: Our objectives were to determine the frequency of HER2 expression in urothelial carcinoma, to identify the association between HER2 expressions with grade of the tumor and to compare the expression patterns/ score of HER2 in low grade and high grade urothelial carcinoma. Material and Methods: This cross-sectional study was conducted in Department of Histopathology, Shaheed Zulfiqar Ali Bhutto Medical University, Pakistan Institute of Medical Sciences. Total 104 urothelial carcinoma cases of urinary bladder were selected. Of these, 52 cases were of low grade and 52 were of high grade. Immunohistochemistry for HER2 was applied on these cases and their subsequent expression and scores were noted. Results: Of the 104 cases, 87.5% were males and 12.5% were females. Mean age was 58.8 years with standard deviation of 11.9 years. Lamina propria invasion was seen in 58 out of 104 cases. HER2 expression was seen in 42.3% of urothelial carcinoma. Forty eight percent of high grade and 36.5% of low grade cases showed HER2 positivity. Among cases without lamina propria invasion, 32.6% were HER2 positive, while among cases with lamina propria invasion, 50% were HER2 positive. Conclusion: HER2 expression was significantly associated with high grade carcinoma and lamina propria invasion. No significant association was found between grade of tumor and score of HER2.